Sistem Latihan Program Pembangunan dan Kepimpinan Pelajar (i-LPPKP) / Nur Hazirah Ab.Aziz - Ab.Aziz, Nur Hazirah (2011)
Nowadays, there are many systems and applications had been migrated to the web based in the world. For this time, data of students’ attendance for Latihan Program Pembangunan Dan Kepimpinan Pelajar (LPPKP) will be stored manually by administration and students should use attendance card as evidence they are attending the programme session and should keep it as long as they are studying at UiTM. If the attendance card is lost or damage they could be considered as absent that programme and they should repeat it for the next semester. This is because these programmes are compulsory activities and each student should be involved. Therefore, the Purpose of this project is to help the administration and student to manage data of attendance in Latihan Program Dan Pembangunan Pelajar (LPPKP) so that it will be appropriate and systematic. By using this system, students do no need to bring attendance card during programme sessions but they just need to access this system online to check their attendance. Administration side also able to store the data of attendance of student and can trace students who absent the programme or not completed their LPPKP programme. In addition it would be help administration to manage attendance of facilitators. Security aspect will be implemented to this system such as password to enter this system. The system architectures that are used to develop this system are XAMPP which are combination of Apache, Web Server and PhpMyAdmin. This system is using PHP programming language and uses the MySQL for the database.